2016
DOI: 10.1091/mbc.e16-05-0265
|View full text |Cite
|
Sign up to set email alerts
|

RIC-3 phosphorylation enables dual regulation of excitation and inhibition ofCaenorhabditis elegansmuscle

Abstract: Excitation–inhibition balance is essential for normal brain function. Calcineurin-dependent dephosphorylation of RIC-3, a chaperone of nicotinic acetylcholine receptors, disinhibits GABAA receptors, enabling fine-tuning of excitation–inhibition balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…RIC‐3 Ser164 was shown to be phosphorylated by a casein kinase II homolog, KIN‐10, and dephosphorylated by the calcium calmodulin‐dependent phosphatase, Calcineurin homolog, TAX‐6. Results of this study suggested a role for RIC‐3 phosphorylation in homeostatic control of excitation‐inhibition balance (Safdie et al., 2016).…”
Section: Many Proteins Are Needed To Make Acetylcholine Receptorsmentioning
confidence: 78%
“…RIC‐3 Ser164 was shown to be phosphorylated by a casein kinase II homolog, KIN‐10, and dephosphorylated by the calcium calmodulin‐dependent phosphatase, Calcineurin homolog, TAX‐6. Results of this study suggested a role for RIC‐3 phosphorylation in homeostatic control of excitation‐inhibition balance (Safdie et al., 2016).…”
Section: Many Proteins Are Needed To Make Acetylcholine Receptorsmentioning
confidence: 78%
“…The C. elegans neuromuscular system, where both excitatory (cholinergic) and inhibitory (GABAergic) motor neurons regulate muscle activity, provides a suitable and complementary model for mechanistic studies of E/I imbalance (Stawicki et al, 2011; Safdie et al, 2016; Zhou et al, 2017). In our system, unc-2(zf35gf) mutations led to a modest increase in RAB-3 expression in the neurites of both excitatory and inhibitory motor neurons, consistent with the notion that increased Ca 2+ influx may potentiate the recruitment of synaptic vesicles (Gracheva et al, 2008; Han et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Genes that were upregulated in C. elegans but downregulated in the soleus include those involved in DNA repair (Nsmce1) [63], and the unfolded protein response (Shq1), suggesting increased damage response in C. elegans. Genes that are downregulated in C. elegans but upregulated in the soleus are involved in muscle excitability (Ric3) [64] and synaptic signaling (Syt12, Ric3, Htr7) [64][65][66] which may impact muscle contraction if globally upregulated in neurons. Downregulated in C. elegans were Dpp4, a gene encoding a multi-functional transmembrane protein involved in glucose uptake [67], and Plce1 involved in growth and differentiation [68].…”
Section: Comparison Between C Elegans and Mouse Slow Twitch Muscle Soleusmentioning
confidence: 99%